(untitled) (Хабаршы. Психология және социология сериясы, 2019)
In this paper I am going to consider some of the moments where knowledge has facilitated progress and social development throughout human civilization. In order to survive, human beings need complex adaptive system that can come only through knowledge of the habitat and the people around. Obviously this is a huge task to embark on in the scope of limited time and space of this volume, therefore there are bound to be some gaps in my observations of how knowledge has shaped societies and how it continues to enhance human civilizations across time and space. Although this volume does not intend to give the role of knowledge a scientific precision, all efforts will only concentrate on a few things that are of interest to me; chiefly human resilience and capability to surmount the challenges of modern society i.e. raging inequality; intense poverty; pervasive injustice; forced migration and resettlement; and worse of all, irreversible environmental degradation. Against this backdrop, the article features the knowledge of eminent scholars on the theme: Doorman, 2015; Dave & Kobayashi, 2018; Giddens, 2014; Gupta, Orlovskiy, 2017; Schulz, 2017; The Econ- omist, 2018; Bank of England, 2014; ICG, 2017. Including Tim Kohler, 2016, lead author and Regents professor of archaeology and evolutionary anthropology at WSU, who noted that The United States currently has one of the highest levels of inequality in the history of the world. In this same context the article draws on the largest and most comprehensive study of its kind that gathered data from 63 archae- ological sites or groups of sites, comparing house sizes within each site to illustrate common measures of inequality. The researchers saw disparities in wealth mount with the rise of agriculture, specifically the domestication of plants and large animals, and increased social organization. The findings have profound implications for contemporary society, as inequality repeatedly leads to social disruption, even collapse.